Chemistry-Assisted Proteomic Profiling of O-GlcNAcylation - Zhu, Qiang; Yi, Wen (Frontiers in Chemistry, 2021)
The modification on proteins with O-linked N-acetyl-β-D-glucosamine (O-GlcNAcylation) is essential for normal cell physiology. Dysregulation of O-GlcNAcylation leads to many human diseases, such as cancer, diabetes and neurodegenerative diseases. Recently, the functional role of O-GlcNAcylation in different physiological states has been elucidated due to the booming detection technologies. Chemical approaches for the enrichment of O-GlcNAcylated proteins combined with mass spectrometry-based proteomics enable the profiling of protein O-GlcNAcylation in a system-wide level. In this review, we summarize recent progresses on the enrichment and proteomic profiling of protein O-GlcNAcylation.